An intuitive methodology for website design. (24th April 2006) - Chong, P. Pete; DeVries, Peter; Chang, Ming
Software tools help us manage web content and website performance, yet we still see poorly designed websites with inappropriate content. A five step entity relationship approach to the systems development life cycle is proposed for developing new websites. This technique bridges the 'communications gap' between non-technical users and web developers.